Pharmacist behavior of halal labelization on pharmaceutical product - Ach. Syahrir; Abdul Rahem; Adistiar Prayoga (Journal of halal product and research (JPHR), 2019)
The survey of the research and development center of Ministry of Religion (Kemenag) of Indonesia in 2013 concluded that public awareness to consume halal products was at a high level. Although the government guaranteed halal products for the customer, the implementation is still not fully implemented. “Halal” status of the pharmaceutical product in Indonesia is still in doubt. The indicator is that 90 percent of the pharmaceutical industry's raw materials are imported materials, that have no guaranteed halal system for these products. In particular, pharmacists have an important role in the preparation of halal pharmaceutical products. Therefore, a study conducted to analyze the pharmacists' behavior regarding halal labeling of pharmaceutical products. This study focused on the behavior of pharmacists in Malang City who are members of the Indonesian Pharmacist Association/Ikatan Apoteker Indonesia (IAI) with the survey method. The objective of this study was to obtain an overview of the perception of the pharmacist on halal labeling in pharmaceutical products in Malang City. The research instrument was a questionnaire. Descriptive statistics ware used to analyze data. The results showed that pharmacists in the city of Malang accepted and strongly agree on halal labeling of pharmaceutical products.